2022
DOI: 10.1109/access.2022.3200753
|View full text |Cite
|
Sign up to set email alerts
|

Research on Technological Divisive Faultlines in Cliques: Evidence From China’s Biomedical Industry Innovation Network

Abstract: Social identity theory and self-classification theory provide theoretical supports for explaining the formation and action of the technological divisive faultlines. The purpose of this study is to explore the effects of technological divisive faultlines on a clique's innovation performance and the moderating effects of geographical proximity and closeness centrality. The data of 119 firm alliance and 351 firms in cliques are collected in China's biomedical industry from 2010-2017. Then, we perform the negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Third, we check and update the firms' business registration name, the established time of the above firms participating in the alliance through the official website of Qichacha (https://www.qcc.com/) and so on. Fourth, we judge whether a firm belongs to the new energy industries alliance by two criteria as follows (Zhao et al , 2022): At least a firm in the alliance belongs to the new energy industries (i.e. wind energy industries, solar energy industries, biomass energy industries, geothermal energy industries, wave energy industries, ocean current energy industries and tidal energy industries). The alliance is engaged in new energy industries. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, we check and update the firms' business registration name, the established time of the above firms participating in the alliance through the official website of Qichacha (https://www.qcc.com/) and so on. Fourth, we judge whether a firm belongs to the new energy industries alliance by two criteria as follows (Zhao et al , 2022): At least a firm in the alliance belongs to the new energy industries (i.e. wind energy industries, solar energy industries, biomass energy industries, geothermal energy industries, wave energy industries, ocean current energy industries and tidal energy industries). The alliance is engaged in new energy industries. …”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, some scholars put forward or summarized their concept definitions according to social network theory and existing research. For example, Zhao et al (2022) thought that ED can measure the closeness of connections among members in a network. Burt (1992) put forward that a structural hole is a relationship of nonredundancy between two contacts and pointed out that it can be measured by effective size, efficiency, constraint and hierarchy.…”
Section: Ego-network Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Building successful technological capabilities to have a niche in the market has been gripped by incumbents and startups [21]. Previous research [22][23] has shown that most citations flow between a few firms in the network, and these significant firms are likely to drive activity in the market. The previous research formulated the multivariate analysis model to develop the organization innovation relationship, briefed in Table I.…”
Section: Related Workmentioning
confidence: 99%
“…Closeness centrality is the measure that scores each node based on their "closeness" to all other nodes in the network. It stands for the convenience and ease of connections between the focused node and rest of the nodes in the network [22]. Closeness centrality is determined by calculating the average inverse distance (distance) between a node and every other node in a network.…”
Section: ) Closeness Centralitymentioning
confidence: 99%